The Floods Cause Diarrhea and Acute Hemorrhagic Conjunctivitis in China: A Literature Review - Fitrotul Ainiyyah Azzahroh (Faculty of Medicine - Universitas Pembangunan Nasional Veteran Jawa Timur, 2025)
Background. Floods in China increase the risk of waterborne diseases, particularly diarrheaand Acute Hemorrhagic Conjunctivitis (AHC), due to contaminated water, poor sanitation, and overcrowded shelters. Method. This literature review analyzes studies from 2020–2025 using the PICO method, focusing on flood exposure and disease morbidity in affected regions. Data were collected from PubMed, Google Scholar, Garuda, and Scopus. Discussion. Floods significantly contribute to increased cases of diarrhea and Acute Hemorrhagic Conjunctivitis due to contamination of drinking water and poor sanitation in affected areas. Environmental factors such as high temperatures and humidity further exacerbate disease transmission. Crowded living conditions in evacuation shelters accelerate the spread of infections. The study highlights the importance of sanitation, clean water access, public education, and healthcare preparedness in mitigating flood-related disease outbreaks. Conslusion. Floods in China pose severe public health risks, particularly increasing the incidence of diarrhea and Acute Hemorrhagic Conjunctivitis. Effective prevention strategies, including improved water sanitation, hygiene education, and infrastructure resilience, are essential to reduce disease burdens in flood-prone regions. Strengthening disaster response mechanisms and public health interventions can help minimize future health impacts caused by flooding.